Correlates of low birth weight in term pregnancies: a retrospective study from Iran - Tavafian Sedigheh; Vahdaninia Mariam; Montazeri Ali (BMC, 2008)
Abstract Background Low birth weight (LBW) is considered as a major multifaceted public health concern. Seventy-two percent of LBW infants are born in Asia. An estimation of 8% LBW infants has been reported for Eastern Mediterranean region including Iran. This study investigated contributory factors of LBW in singleton term births in Tehran, Iran. Tehran is a multicultural metropolitan area and a sample from the general population in Tehran could be regarded as a representative sample of urban population in Iran. Methods This was a retrospective study using data from 15 university maternity hospitals in Tehran, Iran. Data on all singleton term births in these hospitals were extracted from case records during a one calendar year. Study variables included: maternal age, maternal educational level, history of LBW deliveries, history of preterm labor, cigarette smoking during pregnancy, number of parities, chronic diseases and residential area (Tehran versus suburbs of Tehran). In order to examine the relationship between LBW and demographic and reproductive variables the adjusted logistic regression analysis was performed. Results In all, data for 3734 term pregnancies were extracted. The mean age of women was 25.7 (SD = 5.3) years and 5.2% of term births were LBW. In addition to association between LBW and maternal age, significant risk factors for LBW were: history of LBW deliveries [adjusted odds ratio (OR) = 2.53, 95% confidence interval (CI) = 1.06-6.03], smoking during pregnancy (OR = 4.64, 95% CI = 1.97-10.95) and chronic diseases (OR for hypertension = 3.70, 95% CI = 2.25-6.06, OR for others = 2.04, 95% CI = 1.09-3.83). Conclusion The findings indicate that in addition to maternal age, history of LBW deliveries; smoking during pregnancy and chronic diseases are significant determinants of LBW in this population. This is consistent with national and international findings indicating that maternal variables and risk behaviors during pregnancy play important roles on LBW.